Stability and Change in Men’s Intimate Partner Violence and Substance Use in Early Adulthood - Lee, Hyanghee (Journal of interpersonal violence, 2023)
Despite substantial evidence of the role of substance use in intimate partner violence (IPV), little is known about the impact of substance use on stability and change in the experience of IPV as both a perpetrator and a victim. Using an ethnically diverse sample of 232 men in early adulthood (mean age = 29.1, SD = 0.91), this study defined typologies of IPV based on men’s reports of both perpetration and victimization; examined the potential impact of substance use, including alcohol and marijuana use, on IPV typologies over two measurement occasions; and quantified stability and change in these typologies over time. Patterns of IPV were characterized by three classes at each time point: no IPV, psychological aggression, and physical aggression. Men’s regular marijuana use was associated with physical aggression contemporaneously and prospectively. Partner’s problem alcohol use was associated with psychological aggression contemporaneously, suggesting that women’s problem alcohol use could be a risk factor for their own and their partner’s IPV perpetration. IPV appeared to remain somewhat stable over time with 67% of men remaining in the same IPV class. Among those who did transition from one typology to another, it was most often to a less severe IPV typology. Regular marijuana users were more likely to be in the physical aggression typology rather than the no IPV typology, with a higher probability of transitioning to a more severe IPV typology than nonusers. The present study has implications for prevention and intervention efforts by its ability to identify men who are at greatest risk for continued or increased violence and underscores that men’s marijuana use may exacerbate IPV.